BBS News (Bangladesh Journal of Bioethics, 2017)
Training programme on “Research Methodology”Planning, Monitoring & Research Division of DGHS with technical support of Bangladesh Bioethics Society (BBS) and American University of Sovereign Nation (AUSN, USA) organized a three days Training programme on “Research Methodology” on 3-5 December, 2017 at Conference Room, DGHS (1st floor, Old Building). Graduation Ceremony: Following Members of BBS have been graduated from AUSN, USA in 2017 and honored by BBS through a programme.PhD (Bioethics, Sustainability and Global Public Health)Prof Shamima Parvin Lasker, Professor & Head of Anatomy, MH Samorita Medical College, Dhaka – She is the 2nd PhD holder and 1st Female PhD from AUSN. Master of Bioethics and Global Public Health Dr Tonmoy BiswasTanya AhmedTamjida Ahmed